Pengembangan Bahan Ajar dalam Proses Pembelajaran - Srihartini, Yusi; Noerlitasari, Noerlitasari; Yuningsih, Andri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Education is a systematic process aimed at enhancing students' abilities in various aspects, including knowledge, skills, and attitudes. One key element in education is teaching materials, which serve as tools for teachers to deliver content and as a medium to facilitate students' learning experiences. The development of high-quality teaching materials that meet the needs of students is crucial in improving the effectiveness of learning. In the digital age, technology-based teaching materials, such as interactive e-books and educational videos, have become increasingly relevant. The development of teaching materials must consider pedagogical principles such as relevance, diversity, interactivity, simplicity, and evaluation. However, challenges in developing teaching materials, such as budget limitations, lack of teacher training, and unequal access to technology, require solutions involving collaboration between the government, private sector, and other education stakeholders. Through teacher training, the use of open educational resources, and partnerships among various parties, the development of effective and inclusive teaching materials can be achieved, supporting the attainment of quality education for all students.